DRIED SUS SUBSTITUTION OF MILLET FLOUR AS A DIVERSIFICATION EFFORTS OF LOCAL FOOD BASED PASTRY PRODUCTS - Dewi Eka Murniati, Syifa Mutiah Syahidah (Prosiding Pendidikan Teknik Boga Busana, 2020)
Dried sus is a snack which can be bought on the market whose main ingredients are wheat flour, butter, eggs, water and salt which are in small sizes and baked, the price of dried sus is quite affordable. Dried sus is one type of pastry product commonly called choux paste, in addition to many other types of pastry products such as danish and puff pastry but all use flour as the main ingredients, this is because pastry products require gluten which is only available in wheat flour in order to have good product results. Millet is a non-rice cereal food plant. Millet has small-sized seeds, millet including minor economic plants but has a nutrient content similar to other food plants such as rice, corn, wheat, and other grain plants. Millet is the main source of energy, protein, vitamins and minerals for the millions of poorest people in the area where millet is cultivated. Millet is gluten free grain and the only grain that maintains alkaline properties after cooking. These components can affect the physical properties of dry matter such as color, taste, and organoleptic properties of dried sus. The main ingredients of this dried sus are medium protein wheat flour and the ingredients to make dried sus substituted with millet flour are butter, margarine, egg, water, salt, baking powder, cheddar cheese. The study design used was a randomized block design (RBD) with a single factor, namely the substitution rate of flour by millet flour with 3 levels, namely 15%, 30%, and 40%. Keywords: dried sus, millet flour